MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA KELAS Xc MAN 2 PARINGIN PADA PEMBELAJARAN REAKSI REDOKS DENGAN METODE TOTUR SEBAYA - Zulfah Magdalena (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2013)
The reasearch problem at junior high school  level is teacher-center learning, monotonous, and less interactive. The classroom action research implementing peer interactions method on redox reaction concept was conducted. The  research purposes are to increase student intrest and learning outcome to the implementation of peer-interactions method. This action research class that were invoved 22 students class Xc of MAN 2 Paringin as subject research. It was found that student’s comprehention in mastery learning increased from 40,91% at first cycle to 86,39% at second cycle, student’s intrest in very good category in learning process.  Key word : Peer-interactions method,  student intrest and learning outcome, redox reactions.